(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
information technology is now used everywhere. It is clear that such an important area of human life as health cannot be left out. The latest digital developments have a positive impact on the development of the most promising ways of organizing medical care for the population around the world. At the same time, the effective construction of information technology infrastructure is becoming more important. Many countries have been actively using innovations in the field of medicine for a long time. This article covers information about the share of information and communication technologies in medicine and the orni in the fields of Medicine.